UJi Antiinflamasi Kombinasi Ekstrak Etanol Buah Pare Dan Okra Hijau dengan Metode Penghambatan Denaturasi Protein - Dita Mazifa Rosita (Fakultas Farmasi, 2025)
Inflammation is the body's response to infection and tissue injury. Bitter melon (Momordica charantia) and green okra (Abelmoschus esculentus) are two medicinal plants that are believed and have been studied as anti-inflammatory therapy. The purpose of this study was to determine the anti-inflammatory activity the combination of bitter melon and green okra ethanol extracts through protein denaturation inhibition method. Single protein denaturation inhibition test was used to obtain the IC50 value of each extract, the value was used to determine the combination dose (1, ½, ¼, 1/8 IC50). Based on the single test results, bitter melon ethanol extract has better anti-inflammatory activity compared to green okra fruit with IC50 value of bitter melon extract 57.114 ± 2.263 and green okra 95.052 ± 0.471 μg/mL. The combination with the best protein denaturation inhibitory activity of 73.868% was obtained from the combination of bitter melon 57 μg/mL and okra 95 μg/mL. The Combination Index (CI) calculation results showed an intermediate synergistic effect on the combination of bitter melon and green okra extract concentrations (28.5 µg/mL and 95 µg/mL) and (57 µg/mL and 95 µg/mL). Based on these results, it can be concluded that the combination of bitter melon and green okra ethanol extracts has potential as an anti-inflammatory agent judging from the activity of inhibiting protein denaturation and its synergistic effect.
Reaploud Repository February_Hasyim
Keywords: Anti-inflammatory; protein denaturation inhibition; synergistic; bitter melon; green okra